Amino Acid Utilization May Explain Why Bemisia tabaci Q and B Differ in Their Performance on Plants Infected by the Tomato yellow leaf curl virus - Guo, Litao; Su, Qi; Yin, Jin; Yang, Zezhong; Xie, Wen; Wang, Shaoli; Wu, Qingjun; Cui, Hongying; Zhang, Youjun (Frontiers in Physiology, 2019)
To make plants more attractive to vectors of viruses, plant-infecting viruses can alter host plant physiology. The recent outbreaks of Tomato yellow leaf curl virus (TYLCV) relate to the spread of its primary vector, the whitefly Bemisia tabaci. Here, we investigated the question of whether the better performance of B. tabaci Q, relative to that of the B biotype, on TYLCV-infected tomato plants could be explained by differences in the ability of the B. tabaci Q and B to obtain free amino acids from the virus-infected plants. We found that the TYLCV infection of tomato plants significantly affected the mole percentage (mol%) of free amino acids in the phloem sap of the tomato plants and the mol% of free amino acids in B. tabaci adults and B. tabaci honeydew. The TYLCV infection caused the mol% of a larger number of free amino acids to rise in B. tabaci Q than in B, and the analysis of honeydew indicated that, when feeding on TYLCV-infected plants, B. tabaci Q was better able to use the free amino acids than B. tabaci B. The results suggest that B. tabaci Q is better adapted than B to feed on TYLCV-infected plants, and that TYLCV alters the B. tabaci B–Q competitive interaction in favor of Q.